Cryptotanshinone, an orally bioactive herbal compound from Danshen, attenuates atherosclerosis in apolipoprotein E‐deficient mice: role of lectin‐like oxidized LDL receptor‐1 (LOX‐1). (27th February 2015) - Liu, Zhiping; Xu, Suowen; Huang, Xiaoyang; Wang, Jiaojiao; Gao, Si; Li, Hong; Zhou, Changhua; Ye, Jiantao; Chen, Shaorui; Jin, Zheng‐Gen; Liu, Peiqing
Abstract : Background and Purpose: Cryptotanshinone (CTS) is a major bioactive diterpenoid isolated from Danshen, an eminent medicinal herb that is used to treat cardiovascular disorders in Asian medicine. However, it is not known whether CTS can prevent experimental atherosclerosis. The present study was designed to investigate the protective effects of CTS on atherosclerosis and its molecular mechanisms of action. Experimental Approach: Apolipoprotein E‐deficient (ApoE −/− ) mice, fed an atherogenic diet, were dosed daily with CTS (15, 45 mg kg −1 day −1 ) by oral gavage. In vitro studies were carried out in oxidized LDL (oxLDL)‐stimulated HUVECs treated with or without CTS. Key Results: CTS significantly attenuated atherosclerotic plaque formation and enhanced plaque stability in ApoE −/− mice by inhibiting the expression of lectin‐like oxLDL receptor‐1 (LOX‐1) and MMP‐9, as well as inhibiting reactive oxygen species (ROS) generation and NF‐κB activation. CTS treatment significantly decreased the levels of serum pro‐inflammatory mediators without altering the serum lipid profile. In vitro, CTS decreased oxLDL‐induced LOX‐1 mRNA and protein expression and, thereby, inhibited LOX‐1‐mediated adhesion of monocytes to HUVECs, by reducing the expression of adhesion molecules (intracellular adhesion molecule 1 and vascular cellular adhesion molecule 1). Furthermore, CTS inhibited NADPH oxidase subunit 4 (NOX4)‐mediated ROS generation and consequent activation of NF‐κB in HUVECs. Conclusions and Implications: CTS was shown to have anti‐atherosclerotic activity, which was mediated through inhibition of the LOX‐1‐mediated signalling pathway. This suggests that CTS is a vasculoprotective drug that has potential therapeutic value for the clinical treatment of atherosclerotic cardiovascular diseases. Linked Articles: This article is part of a themed section on Chinese Innovation in Cardiovascular Drug Discovery. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2015.172.issue-23